Model pembinaan karakter masyarakat maju: Analisis terhadap peranan Tun Dr. Mahathir Mohamad - Abdul Aziz, Abdul Rahman (2012)
The title of the paper is “Model of Character Building for Progressive Society: An analysis of the role of Tun Dr. Mahathir Mohamad”.Dr. Mahathir Mohamad, the fourth Prime Minister of Malaysia, was at helm of the country's administration for 22 years.Prior to his appointment in 1974 as Minister of Education in Tun Razak's cabinet, he wrote Malay Dilemma (1970).In his magnum opus, he concluded Malays were backward because of two main factors.Firstly, due to biogenetic factor, Malays as a race, lack of cross-breeding, lack of migrations, therefore they dominate only at the local scene. Secondly, sociogenetic factor, the value systems of the Malays were traditional, and they could not afford to think bigger than the village scene. Dr. Mahathir, concluded that the government should intervene to raise the living standard of the Malays. Dr. Mahathir played his political role as a leader that tried all sorts of means to inculcate core values pertinent for self-improvement.The core values were important for character building.Therefore, in this article, Dr. Mahathir's thought on character building were discuss and bring into contexts with three main spheres, namely, cultural value-system, discipline and organisation, and management.Dr. Mahathir's suggestions were based on virtues derived from civilisations which was proven successful.